Searching for the Historical Jesus: Examining the Work of John Dominic Crossan and Marcus J. Borg - O'Keeffe, Michael E. (Horizons, 1997)
The movement broadly defined as the "New Quest for the Historical Jesus" represents one of the more important areas where academic scholarship has had a direct bearing on popular religion. Although many forces have been instrumental in this development, perhaps the most important has been the popularizing work of the Jesus Seminar, under the direction of Robert Funk. This essay examines two of the premier scholars associated with the Seminar, namely, John Dominic Crossan and Marcus J. Borg. It examines their methodologies and central christological claims, and gives special consideration to Borg's addition of a "theo-cosmic level" that distinguishes his work from Crossan's.